The impact of EU enlargement on the agricultural output and income in the member states - Kobus, Paweł (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2008)
The paper presents an analysis of the impact of the EU enlargement in 2004 on the agricultural output and incomes of the EU Member States. The main aim of the study is to test the significance of difference of reaction to enlargement in three distinct groups of members, namely the ‘old’ fifteen Member States, the ‘new’ ten Member States which accessed the EU on May 1st 2004, and the two ‘newest’ Member States, i.e. Romania and Bulgaria which accessed the EU on January 1st 2007. For the purpose of description of different countries behaviour a linear mixed model was applied.